Unifying K-12 Learning Processes: Integrating Curricula through Learning - Michael J. Bosse; Elizabeth A. Fogarty (Arizona State University, 2011)
This study was designed to examine whether a set of cross-curricular learning processes could be found in the respective K-12 US national standards for math, language arts, foreign language, science, social studies, fine arts, and technology. Using a qualitative research methodology, the standards from the national associations for these content areas were narrowed to thirteen distinct learning processes consisting of both singleton and hybridizations of several learning processes. The determination of a superset of learning processes will allow researchers, curriculum developers, and teachers both in and outside the United States to better understand the relatedness of certain types of instruction, irrespective of content area; develop novel techniques regarding content integration within instruction; better develop students' capacities for 21st century learning; and develop new standards more attuned to these process standards.  This investigation concludes with a call for National Learning Processes Standards.